(untitled) (Revista Ifes Ciência, 2022)
Wind Energy, considered a stable alternative, may be implemented in cities by means of vertical axis wind turbines, which have better performance against turbulent flow compared to horizontal axis turbines. However, this type of turbine has not evolved technologically significantly in the last few centuries, being the horizontal axis turbines more studied and developed, due to the theoretical better efficiency of these turbines, which creates room for improvement. Therefore, vertical axis wind turbine will be studied and the performance of some enhancements will be analyzed aiming a more efficient harvesting of wind energy. In this regard, a flow augmentation system is proposed to be integrated with the wind turbine. In addition, the Lenz 2, S815 and JShaped airfoil shapes will be analyzed by Computational Fluid Dynamics – CFD technique on the ANSYS software for comparison of static torque generated by the wind turbine against wind flow for different angular positions of the turbine. Analyzing the gains obtained with the integration of the flow augmentation system proposed, achieving, this way, results regarding to cut in speed and overall efficiency of the shapes. Results show that the use of the convergent omnidirectional nozzle guide increased the overall static torque of all turbines, which would decrease the cut in speed, as well as its increased effectiveness on drag driven airfoils.